[PP.23.13] ANALYSIS OF ELIGIBILITY CRITERIA FOR RENAL SYMPATHETIC DENERVATION. (September 2016) - Fulcheri, C.; Rabbia, F.; Testa, E.; Berra, E.; Di Monaco, S.; Covella, M.; Pappaccogli, M.; Perlo, E.; Veglio, F.
Abstract : Objective: Resistant hypertension (RH) is a rare condition that affects approximately 10% of hypertensive population, it's defined as blood pressure (BP) > 140/90 mmHg despite three full doses antihypertensive drugs including a diuretic. True RH is confirmed when pseudo-hypertension, secondary hypertension or poor adherence are excluded. Percutaneous radio-frequency catheter-based renal sympathetic denervation (DRN) is one of the most used invasive treatments for these patients. The goal of the study is to assess the percentage of eligibility to DRN and analyze the exclusion criteria in a group of resistant hypertensive patients. Design and method: We retrospectively analyzed data of 35 patients (63% female) referred to our Hypertension Unit between June 2011 and June 2014. We considered eligible for DRN subjects with office systolic blood pressure > = 160 mmHg and patients with severe hypertension treated with fewer drugs for poly-intolerances/allergies. Secondary hypertension form and white coat hypertension were excluded. Patients with confirmed true resistant hypertension underwent CT angiography in order to check the renal anatomic criteria of eligibility to the DRN. Results: 35 caucasian patients (63% female) referred to our Hypertension Unit between June 2011 and June 2014 for DRN assessment. At the first evaluation median systolic and diastolic office BP were 179 ± 25 mmHg and 105 ± 20 mmHg; six month later, after appropriate changes in lifestyle and drug therapy, systolic/diastolic office BP was reduced of 18/8 mmHg (p < 0.05). In the most of cases, patients had to BP control with introduction of antialdosteronic (35%). In our sample, 27 patients were considered unsuitable for the DRN for many reason: blood pressure control with optimization of drug therapy (52%), evidence of white coat effect (22%), secondary hypertension (22%), lack of true resistant hypertension (18%), absence of consent to the procedure (29%). Conclusions: A carreful patients selection in Specialistic Center is necessary before DRN; indeed frequently a good BP control is obtained with appropriate drug therapy changes and exclusion of secondary forms.